1997
DOI: 10.1002/(sici)1097-0290(19970205)53:3<304::aid-bit9>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate uptake kinetics byAcinetobacter isolates

Abstract: Acinetobacter isolates from activated sludge treatment plants of forest industry were used as model organisms for polyphosphate accumulating bacteria to study excess phosphate uptake by the overplus phenomenon as well as luxury uptake of phosphate during growth. The initial, rapid phosphate uptake by the phosphorus‐starved Acinetobacter isolates (the overplus phenomenon) followed the Michaelis‐Menten model (maximum initial phosphate uptake rate 29 mg P g−1 dry mass (DM) h−1, half‐saturation constant for excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The optimal cultivation time for P removal by M. circinelloides was 5 days. Organisms typically remove P through three patterns: by the overplus phenomenon after P limitation, in the declining phases of growth, or by luxury phosphate uptake in the growth phase without P starvation [15]. The growth curve showed that M. circinelloides accumulated polyphosphate during growth without P starvation, which implied that M. circinelloides accumulated P by luxury phosphate uptake.…”
Section: Neisser Stain To Confirm Phosphate Accumulation Of M Circinmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal cultivation time for P removal by M. circinelloides was 5 days. Organisms typically remove P through three patterns: by the overplus phenomenon after P limitation, in the declining phases of growth, or by luxury phosphate uptake in the growth phase without P starvation [15]. The growth curve showed that M. circinelloides accumulated polyphosphate during growth without P starvation, which implied that M. circinelloides accumulated P by luxury phosphate uptake.…”
Section: Neisser Stain To Confirm Phosphate Accumulation Of M Circinmentioning
confidence: 99%
“…The growth curve showed that M. circinelloides accumulated polyphosphate during growth without P starvation, which implied that M. circinelloides accumulated P by luxury phosphate uptake. Organisms with luxury phosphate uptake capability have gained great interest owning to their high P removal efficiencies [15]. Furthermore, this fungal strain can continuously uptake phosphate from media during its growth without the need for a complicated aeration operation (shaking at 150 rpm in this study).…”
Section: Neisser Stain To Confirm Phosphate Accumulation Of M Circinmentioning
confidence: 99%
“…Phosphate uptake kinetics by Acinetobacter isolates were studied by Pauli and Kaitala (1997). Ha]f-saturation constants were determined to be ] 7 and 0.4-6.0 mg/L as phosphorus for phosphate uptake and cell growth, respectively.…”
Section: Ks Coefficientsmentioning
confidence: 99%
“…In a pure culture study using A. twoffii and A. calcoaceticus, the phosphorus release under anaerobic conditions was not always related to the amount of VFA or phosphorus consumed, and phosphorus uptake under aerobic conditions was independent of phosphorus-release rates (Rustrian et at., 1997). Pauli and Kaitala (1997) studied phosphate uptake in Acinetobacter, and phosphate uptake followed Michaelis-Menten kinetics with a maximum uptake rate of 29 mg phosphorus/g SS' hand halfsaturation constant of ]7 mglL as phosphorus.…”
Section: Literature Review 1998mentioning
confidence: 99%
“…Typically, a simple unstructured kinetic model is used to describe the interaction between the substrate and the enzyme or microbe. The Michaelis-Menten equation has been widely used to describe substrate depletion by enzymes and nongrowing bacterial suspensions (Betlach and Tiedje, 1981;Pauli and Kaitala, 1997;and Suflita et al, 1983) while the Monod equation has been widely used to describe growth associated substrate consumption (Corman and Pave, 1983;Naziruddin et al, 1995;and Smith et al, 1997). Quantification of the microbe-or enzyme-substrate interaction involves estimating several parameters in the kinetic models using experimental data.…”
Section: Introductionmentioning
confidence: 99%